Thymoquinone Protects against Myocardial Ischemic Injury by Mitigating Oxidative Stress and Inflammation. (25th May 2015) - Ojha, Shreesh; Azimullah, Sheikh; Mohanraj, Rajesh; Sharma, Charu; Yasin, Javed; Arya, Dharamvir S.; Adem, Abdu
Abstract : The present study was aimed at investigating the cardioprotective activity of thymoquinone (TMQ), an active principle of the herb, Nigella sativa, which is used for the management of various diseases. The present study examined the cardioprotective effect of TMQ in isoproterenol- (ISP-) induced myocardial infarction in rats. Myocardial infarction was induced by two subcutaneous injections of ISP (85 mg/kg) at an interval of 24 hr. TMQ (20 mg/kg) was administered orally for 21 days. ISP-treated rats showed depletion of antioxidants and marker enzymes from myocardium along with lipid peroxidation and enhanced levels of proinflammatory cytokines. ISP also induced histopathological alterations in myocardium. Treatment with TMQ prevented the depletion of endogenous antioxidants and myocyte injury marker enzymes and inhibited lipid peroxidation as well as reducing the levels of proinflammatory cytokines. TMQ pretreatment also reduced myonecrosis, edema, and infiltration of inflammatory cells and showed preservation of cardiomyocytes histoarchitecture. The present study results demonstrate that TMQ exerts cardioprotective effect by mitigating oxidative stress, augmenting endogenous antioxidants, and maintaining structural integrity. The results of the present study indicate that TMQ may serve as an excellent agent alone or as adjuvant to prevent the onset and progression of myocardial injury.